EPV 1. Coronal examination plane in transcranial sonography improves the discrimination between Parkinson's disease and essential tremor. Additional benefits by sonographic determination of the tremor frequency. Issue 9 (September 2016) - Richter, D.; Woitalla, D.; Muhlack, S.; Gold, R.; Tönges, L.; Krogias, C.
Abstract : Background: Transcranial sonography (TCS) is a reliable and sensitive diagnostic tool for the discrimination between Parkinson's disease (PD) and essential tremor (ET). Currently, a single axial mesencephalic examination plane is routinely used in the evaluation of Substantia nigra (SN) echogenicity. However, the SN can also be depicted in a second coronal examination plane. In addition, the M-mode tremor frequency determination (M-TFD) represents a further but not yet established sonographic examination tool, which might integrate into the diagnostics of extrapyramidal movement disorders. Aim: To evaluate the usefulness of a new coronal examination plane in discriminating PD from ET, by comparing the predicted values of the established axial examination plane. Furthermore, the diagnostic sensitivity and specificity of combined assessment of TCS and M-TFD are evaluated. Methods: Echogenic areas of the SN of 30 PD patients were determined by TCS using the standard axial as well as coronal planes. In both planes a cut-off-value [c]0, 2 cm[b] was used to define SN-hyperechogenicity (SN+). Tremor frequencies of resting and postural tremor were quantified by a M-TFD examination protocol. Isolated postural tremor with a frequency [c]6 Hz was defined as a typical ET-finding. Results of 30 PD-patients were compared with the findings of 7 ET patients and of 13 healthy controls. Results: Our standardized axial plane TCS protocol showed a sensitivity of 90%, a specificity of 80%, a positive predictive value (PPV) of 87% and a negative predictive value (NPV) of 84% in supporting the diagnosis of PD. Interestingly, the use of the new coronal examination plane revealed even superior values (sensitivity = 93%, specificity = 85%, PPV = 90%, NPV = 89%). The combined sonographic assessment of TCS and M-TFD provided best diagnostic efficacy (sensitivity = 90%, specificity = 95%, PPV = 96%, NPV = 86%). Conclusion: In the present study, the application of a coronal examination plane improved the diagnostic precision of TCS in discriminating PD from ET. In the combination with sonographic determination of tremor frequency by M-TFD best discriminative results are achieved. Thus, the combined usage of coronal TCS and M-TFD should be considered in the future to optimally apply sonography techniques for the evaluation PD and ET.